# math

Find the inverse of each of these functions
a)f(x)=x/x+2
b)f(x)=2x/5-x
c)f(x)=3x/2x+1

1. x =2y/5 -y
5x = 2y -5y
5x = -3y
F(x) = -5x/3

posted by Anonymous
2. 1st one:

if f(x) = x/(x+2) , then y = x/(x+2)

step1: interchange the x and y variables to get the inverse as

x = y/(y+2)

step 2: solve this new equation for y

x = y/(y+2)
xy + 2x = y
xy - y = -2x
y(x-1) = -2x
y = -2x/(x-1) or y = 2x/(1-x)

f^-1 (x) = 2x/(1-x)

now do the same for others following these two steps.

posted by Reiny

First Name

## Similar Questions

1. ### Math - Inverse Functions

Find the inverses of the following functions. y = 3(x - 1)^2, x >= 1 Work: x = 3(y - 1)^2 x = 3(y - 1)(y - 1) x = 3(y^2 - y - y + 1) x = 3y^2 - 6y + 3 And now what do I do!? Please explain and show me how to solve this inverse
2. ### math

consider the functions f(x)=x^3-2 and g(x)=3 sqrt x+2: a. find f(g(x)) b. find g(f(x)) c. determine whether the functions f and g are inverse of each other. I have no clue where to even begin!
3. ### Functions - math

The function f is such that f(x) = a^2x^2 - ax + 3b for x<=(1/2a), where a and b are constants. 1) For the case where f(-2) = 4a^2 - b +8 and f(-3) = 7a^2 - b + 14, find the possible values of a and b. 2) For the case where a =
4. ### Functions - math

The function f is such that f(x) = 2x + 3 for x ≥ 0. The function g is such that g(x)= ax^2 + b for x ≤ q, where a, b and q are constants. The function fg is such that fg(x)= 6x^2 − 21 for x ≤ q. i)Find the values of a
5. ### Math

If the inverses of two functions are both functions, will the inverse of the sum or difference of the original functions also be a function? Explain your reasoning.

What is the inverse of each of the functions defined by the following equations, if the inverse exists. If the inverse does not exist for the largest possible domain, limit the domain so that the inverse will exist. In each case,
7. ### Algebra Help ASAP PLEASE!

((I forgot how to do find inverse functions and this is important)) Find the inverse function of g(x) = 2x + 4. A) g^(-1)(x) = 4x + 2 B) g^(-1)(x) = 2x + 1/2 C) g^(-1)(x) = 1/2x - 2 D) g^(-1)(x) = 2x - 4 I *think* it might be C
8. ### Algebra

Given the functions f(x)=x+5/3 and g(x)=1/f^-1(x)+1, find the value of g(3). The first step would first be to find the inverse of x+1, the denominator of the fraction. I think the inverse would be 1-x. And now we have 1/1-x so we
9. ### End behavior models

Thanks for the help with my previous problems Roger & Leo. It was really helpful. Now I want to know how to find the right and left end behavior models and horizontal tangents for the inverse functions, say y = tan inverse(x) I
10. ### Algebra

How do you find the inverse of functions? for example how would you find the inverse of y= log8 x

More Similar Questions